2011
DOI: 10.1590/s0103-64402011000600014
|View full text |Cite
|
Sign up to set email alerts
|

Removal of oral lichen planus by CO2 laser

Abstract: The aim of this case report is to present a histologically diagnosed oral lichen planus excised by the CO2 laser. Oral lichen planus is a chronic inflammatory mucocutaneous disease of unknown etiology. Different treatments have been used to manage this condition. A 46 year-old female was referred to the Laser Clinic of the Dental School of the Federal University of Bahia to excise a lesion characterized by white patches on the oral mucosa, which was causing pain and burning sensation and had not respond to tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In comparison with previous studies, de Magalhaes et al (2011) reported a patient who was not responsive to corticosteroids for 3 months; the patient was then treated with CO 2 laser and showed no recurrence or pain for 1 year of follow‐up. The study by Matsumoto et al (2019), in which nine patients with 11 sites were treated with CO 2 laser vaporisation, showed a significant reduction in pain and TSS score 1 year after irradiation.…”
Section: Discussionmentioning
confidence: 84%
“…In comparison with previous studies, de Magalhaes et al (2011) reported a patient who was not responsive to corticosteroids for 3 months; the patient was then treated with CO 2 laser and showed no recurrence or pain for 1 year of follow‐up. The study by Matsumoto et al (2019), in which nine patients with 11 sites were treated with CO 2 laser vaporisation, showed a significant reduction in pain and TSS score 1 year after irradiation.…”
Section: Discussionmentioning
confidence: 84%
“…After laser surgery, there is formation of a necrotic zone at the edge of the incision which acts as a scaffolding for re-epithelization. In most of studies, time to re-epithelization ranges between 3 and 6 weeks [11,12]. Laser wounds show delay in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…An association with specific drugs or systemic disorders is well documented, as is its predilection for premalignant transformation (Scully & el-Kom, 1985). There have been many attempts at direct ablation or targeting immune cells in OLP with surgical or excimer lasers, but these have shown limited benefits (de -Junior, Aciole, Santos, dos Santos, & Pinheiro, 2011;Liu, Sun, Yang, & Wang, 2017;Mucke et al, 2015;Trehan & Taylor, 2004). Interestingly, despite any direct correlation of a microbiological aspects in its etiopathology, there are clinical reports on efficacy of aPDT in OLP patients.…”
Section: Photobiomodulation Therapy For Lichen Planusmentioning
confidence: 99%